Prevalence Of Severity Of Child Malnutrition Under Age 5 In India: A State Wise Analysis - Pruthi, Somnath; Sisodia, Tushar Singh (Journal of Neonatal Surgery, 2025)
The present study seeks to draw the attention of policy makers towards critical state of Child health across Indian States and union territories and aims to offer recommendations for formulating nuanced policies targeted to reduce severe child malnutrition using the insights from unit level data of rounds 4 and 5 of National family health survey of India (NFHS 2015-16 to NFHS 2019-21). As per the 5th round of National family health survey (NFHS-5, 2019-21), 5 percent of children under age 5 in India remained stunted, wasted and underweight. The study found that during 2015-16 (4th round) to 2019-21 (5th round), there was 7 percent decline in prevalence of severity of child malnutrition. The study recognizes Meghalaya and Bihar as having the highest percentage of severely stunted children, while Chandigarh and Kerala report the lowest. In addition, this study identifies Gujarat and Maharashtra have the uppermost percentage of children affected by severe wasting, whereas Chandigarh and Puducherry have the lowest. The western most state, Gujarat records the highest percentage of underweight children followed by Bihar, while Manipur and Mizoram report the lowest. Finally, the study suggests that States and U.T.s having critical status of child malnutrition should strengthen Mid-Day Meal, Poshan Abhiyaan and Integrated child development services (ICDS) while improving Immunization, maternal care and sanitation. The lagging states must adopt the best practices of Chandigarh and Kerala